O uso das pregas cutâneas e da circunferência muscular do braço no diagnóstico de desnutrição energético-protéica em pacientes adultos: estudo crítico. - Paiva, S. A.; Godoy, I.; Padovani, C. R.; Geraldo, R. R.; Campana, A. O. (My University, 1992)
The use of anthropometric measurements of triceps (TSF) and subscapular skinfolds (SSF) and mid-upper arm muscle circumference (MAMC) was examined as far as the diagnosis of energy-protein malnutrition (EPM) is concerned. The study was undertaken in five groups of patients (n = 231): arterial hypertension (AH, n = 63), chronic obstructive pulmonary disease (COPD, n = 17), hemodialyzed chronic renal failure (CRF, n = 19), critically ill patients with an acute event (CA, n = 42) and critically ill patients with chronic diseases (CCD, n = 90). The results were compared to those obtained in a group of healthy individuals (control group, n = 102). The control group and the group of patients were allocated in subgroups according to sex and age (less than 50 and more than 50 years). It was expected that significant differences would be found for the anthropometric values between the control subgroups and the COPD, the CRF and the CCD subgroups of patients. For the skinfold thicknesses (TSF and SSF), significant differences were found between CRF, CCD subgroups and the control subgroups under fifty years of age; however, the differences were not significant when the subgroups over fifty were analyzed. Concerning the MAMC, significant differences were found: 1 degree) between the CRF subgroups (males and females) and the control subgroups under fifty years of age; 2 degrees) between the CCD male subgroups (younger and older subgroups) and the respective control subgroups and 3 degrees) between the COPD and the control subgroups.(ABSTRACT TRUNCATED AT 250 WORDS)
The use of skinfolds and of the muscle circumference of the upper arm in the diagnosis of protein-energy malnutrition in adults patients: a critical study
Keywords: adult; aging; anthropometry; arm; chronic kidney failure; chronic obstructive lung disease; comparative study; female; histology; human; hypertension; intensive care; male; muscle; protein calorie malnutrition; sexual development; skinfold thickness; Adult; Aging; Anthropometry; Arm; Comparative Study; English Abstract; Female; Human; Hypertension; Intensive Care; Kidney Failure, Chronic; Lung Diseases, Obstructive; Male; Middle Age; Muscles; Protein-Energy Malnutrition; Sex Characteristics; Skinfold Thickness